Difference of Het Re Level In Thalassemia β Minor And Iron Deficiency Anemia - Yustisia Amalia (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The population was students who were admitted to the University of Dr. Soetomo who came for complete blood count examination. The subjects were students with MCV <80 fl, MCH <27 pq. Subjects who met the inclusion criteria then continued with the calculation of the Mentzer Index and RDW Index, ferritin serum examination using the ECLIA method, hemoglobin electrophoresis examination with micro capillary electrophoresis. By consecutive sampling, 42 samples were obtained, of which 21 subjects diagnosed with iron deficiency anemia and 21 subjects diagnosed with beta thalassemia minor were examined for their Ret-He levels using the flowsitometric method which were then analyzed statistically.From the results of the study concluded that there was a significant difference between the levels of Ret-He in patients with iron deficiency anemia with thalassemia beta minor patients with a cut-off value of 27.30pg